Intersectionality in Housing Research: Early Reflections from a Community-based Participatory Research Partnership - MacDonald, Katie; Dorow, Sara; Klein, Reisa; Kochkina, Olesya (Engaged Scholar Journal, 2024)
This paper discusses early reflections on a project implementing intersectional praxis across the life cycle of community-based participatory research (CBPR). Drawing on our team’s inaugural Co-learning Workshop, which included community and academic partners, we share our initial learnings about developing an intersectional approach to housing security. Specifically, we reflect on three key challenges, or promising puzzles, that emerged as we began our collaboration: co-defining intersectionality (across both theory and implementation), integrating intersectionality into understanding the multi-scaled complexities of housing security, and communicating intersectionality’s relevance to a wider network of actors in housing security policy and programming. Drawing from our learnings, we suggest that an intersectional lens is powerful because it attends to the everyday lived experiences of housing insecurity, the interlocking systemic forms of oppression that create differentiated experiences of housing, and the specific contexts in which structural housing inequities take root.